2015
DOI: 10.1016/j.compositesa.2015.01.022
|View full text |Cite
|
Sign up to set email alerts
|

On tapered warp-free laminates with single-ply terminations

Abstract: Abstract:This article reviews the current state of the art in the design of traditional uni-directional fibre laminate construction; beyond the ubiquitous balanced and symmetric design. A ply termination algorithm is then employed to develop permissible tapered designs, with single-ply terminations and ply contiguity constraints, which are free from undesirable changes in mechanical coupling characteristics.More importantly however, is the fact that all tapered designs have immunity to thermal warping distorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…When A 16 , A 26 0, in-plane shear with extension coupling exists, and in the case when D 16 , D 26 0 out-of-plane bending and twisting coupling appears. According to the international literature (e.g., [1][2][3][4]40]), the used notations for the ABD laminate stiffness matrix are presented in Table 3. In the parametric study, the layer arrangements were assumed in such a way as to check all possible cases of coupling matrix B presented in Table 3.…”
Section: Layer Arrangements With Their Abd Laminate Stiffness Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…When A 16 , A 26 0, in-plane shear with extension coupling exists, and in the case when D 16 , D 26 0 out-of-plane bending and twisting coupling appears. According to the international literature (e.g., [1][2][3][4]40]), the used notations for the ABD laminate stiffness matrix are presented in Table 3. In the parametric study, the layer arrangements were assumed in such a way as to check all possible cases of coupling matrix B presented in Table 3.…”
Section: Layer Arrangements With Their Abd Laminate Stiffness Matrixmentioning
confidence: 99%
“…York analyzed the HTCS design of laminates with non-standard ply angle orientation (+60 • , −60 • , 0 • and 90 • ) [1]. Furthermore, he analyzed new design methods for tapered laminates under various types of load [2]. Shamsudin and York [3] provide in-depth analyses of standard laminate stacking sequences in order to obtain thermally immune structures.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the understanding of stress distribution near ply drops, a number of stress based and energy-release-rate (ERR) based approaches have been proposed to predict delamination onset and growth [1,7,11,12]. Useful optimisation methods of designing a tapered laminates were also presented based on a generic algorithm or stacking sequence tables [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…However, thermal warping distortions are eliminated only when the number of repeats (r) remain large.Recent research has however demonstrated that tailored Non-Crimp Fabric (NCF) designs, based on 0/45 and 0/-45 architectures, can produce fully uncoupled laminates or laminates with Extension-Shearing and/or Bending-Twisting coupling, and that all have immunity to thermal warping distortion [7]. The extent to which tapered laminate designs can be achieved, without introducing unwanted thermo-mechanical coupling, was also investigated through a layer termination algorithm to introduce single-layer [8] or, where necessary, multiple-layer terminations [4,7]. This research followed related studies on laminate design for uni-directional (UD) fibre architectures for fully uncoupled laminates [9], and those with Extension-Shearing [10] and/or Bending-Twisting coupling [11,12].The results presented in this article investigate these four laminate classes constructed from the new NCF architectures, see Fig.…”
mentioning
confidence: 99%
“…Extension-Shearing or E-S coupled, and Extension-Shearing and Bending-Twisting or E-S;B-T coupled warp-free laminate classes are reported inTable 1. Each row corresponds to a particular layer number grouping, nNCF, with NCF layers and the equivalent ply number grouping, nUD, with UD layers are given in parentheses, which correspond to previously derived results[8] with matching ply contiguity (≤ 2) constraint. This ply contiguity is a natural constraint, arising from the NCF architecture, which accounts for the reduced design space.…”
mentioning
confidence: 99%